108 Is the UK underestimating the importance of left ventricular function assessment in contemporary PCI?. (22nd September 2015) - De Silva, K; Webb, I; Sicard, P; Lockie, T; Redwood, S; Perera, D
Abstract : Introduction: The impact of left ventricular ejection fraction (LVEF) on outcome in contemporary percutaneous coronary intervention (PCI) is unclear. The British Cardiovascular Intervention Society (BCIS) audit data suggest that in the UK, only 46% of all patients undergoing PCI have LV function assessment prior to their procedure. The North West Quality Improvement Programme (NWQIP) risk-prediction model does not include LVEF as a potential predictor of adverse outcome. LVEF is also not included in current American and European PCI guidelines. We set out to clarify its impact on early and long-term survival following PCI in a large, contemporary single centre cohort. Methods: Consecutive patients undergoing PCI between 2005 and 2009 at St. Thomas' Hospital, London, UK were included. LVEF was determined by echocardiography or LV angiography and categorised as Good (EF≥50%), Moderate (31–49%) or Poor (≤30%) at the time of PCI. The primary endpoint was 30-day all-cause mortality and the secondary endpoint was long-term all-cause mortality. Predictors of outcome were assessed by univariate and multivariate analyses. Data are mean±SD. Results: Two thousand three hundred and sixty patients who had been categorised according to LVEF at the time of PCI were included (aged 65±11.1 years). 43% presented as acute coronary syndromes. Drug-Eluting stents were used in 53% of cases. 30-day mortality rates were inversely correlated with LVEF, being 0.5%, 2.1% and 8.8% for patients with good, moderate and poor LVEF respectively (p<0.001). The difference in mortality was maintained at 2.2± 1.4 years, (3.4% vs 6.5% vs 15.4% respectively, p<0.001). LVEF was a strong predictor of mortality on univariate analysis and in a multiple regression model incorporating age, acuity of presentation, history of renal dysfunction and cardiogenic shock; 30-day HR 2.47 (95% CI 1.40 to 4.34) and 2.2 years HR 2.00 (95% CI 1.46 to to 2.74). Conclusion: LVEF is a strong predictor of early and long-term outcome following PCI. The importance of LVEF, as a simple method of stratifying risk should be emphasised more strongly in risk-stratification models and included in UK and international PCI guidelines. LV function should be assessed routinely before all PCI procedures.